L'obscène, mode d'emploi Considérations intempestives à l'usage du monde contemporain - Frei, Peter; Labere, Nelly (PrimaLun@, 2022)
Move on ! There is nothing to see ... ...except, according to Facebook, when it comes to Courbet's Origin of the World. While the legendary painting attracts more than 3 million visitors a year at the Musée d'Orsay in Paris, it is still subject to censorship, even legal action, in the brave new world of social media. Far from being anecdotal, the case once again puts the obscene center-stage at a time in which new technologies redefine the public sphere and with it the codes and practices of representation. L'obscène, mode d'emploi ("The Obscene, a Manual") invited scholars and writers to revist the famously troublesome notion of the obscene in its aesthetic, legal and political stakes. The resulting Considérations intempestives à l'usage du monde contemporain ("Untimely Considerations for our Contemporary World") show that the obscene is best understood not as a concept but as a gesture experimenting with both the impact and the medium itself of representation, thereby asking: What does the obscene have to say about the (im-)possibilities of the Digitial Revolution of our time in which the new codes and practices of representation are still being renegociated?